Ultrasensitive Online SERS Detection of Structural Isomers Separated by Capillary Zone Electrophoresis - Negri, Pierre (2014)
A mixture of structural isomers was separated and identified at nanomolar concentrations (~100,000 molecules) by incorporating capillary zone electrophoresis (CZE) with a sheath flow surface-enhanced Raman scattering (SERS) detector. Baseline resolution was obtained from three structural isomers of rhodamine using a planar silver SERS substrate, demonstrating the utility of this approach for trace chemical analysis.